(untitled) (Indian Journal of Case Reports, 2020)
Indiscriminate use of alcohol-based hand sanitizers during the coronavirus-19 pandemic has led to adverse effects on the skin across the globe. We present the case of a 12-years-old child, who developed a skin rash on the dorsal aspect of the hands with overapplication of 70% isopropyl alcohol-based hand sanitizer. On examination, inflamed dark-colored skin with itching was noticed. Based on the history and examination, a diagnosis of “Isopropyl alcohol-based sanitizer-induced irritant contact dermatitis” was made. The application of offending sanitizer was immediately stopped. An improvement was seen 2 weeks after the application of topical corticosteroids and oral antihistamines. No re-challenge was subjected to the child. The Naranjo causality assessment score of six suggested probable association of adverse effect with the use of 70% isopropyl alcohol. It can be concluded that alcohol-based hand sanitization to be reserved for outdoor use, whereas only soap and water should be promoted to be used at home for sanitizing hands. The risk of adverse reactions can be minimized by following the manufacturer’s instructions and reducing the frequency of use of single hygiene products.